Adaptation and Psychometric Test Measurement of The Counseling Self-Estimate Inventory (COSE) Instruments for School Counselors In Indonesia - Ferdian, Flaviana Rinta; Chrisnatalia, Desy; Verina, Vera; Adeline, Maristela (Universitas Muhammadiyah Metro, 2024)
School counselors must have counseling self-efficacy. High self-efficacy in counseling allows school counselors to provide high-quality counseling services, increase the sense of achievement, feel more involved with work, and be confident in their ability to do counseling. Despite the importance of counseling self-efficacy for school counselors, insufficient counseling self-efficacy measurement tools in Indonesia are available. So far, one available self-efficacy measuring tool with good psychometric properties that has been adopted for various countries is the Counseling Self-estimate Inventory (COSE) instrument. However, COSE has not been adapted to the Indonesian language. Due to the rarity of self-efficacy tools for school counselors, this study aims to adapt the COSE instrument to the Indonesian language. The analysis was carried out through reliability and validity tests. The results of the adapted COSE scale into Bahasa Indonesia (for school counselors) were deemed reliable, where each dimension’s reliability is above 0,70. The validity of the adapted COSE scale used content validity with a qualitative method by conducting forward and backward translation processes.